A Comparison of the Psychometric Properties of the Forced Choice and Likert Scale Versions of a Personality Instrument. (March 2015) - Joubert, Tina; Inceoglu, Ilke; Bartram, Dave; Dowdeswell, Kim; Lin, Yin
<x xml:space="preserve">Abstract</x> The present research investigated if an item response theory (IRT)‐scored forced‐choice personality questionnaire has the same normative data structures as a similar version that uses a 5‐point Likert scale instead. The study was conducted using a sample of 349 training delegates who completed both an IRT‐scored forced‐choice and a normative single‐stimulus version of the questionnaire. Results largely supported the scaling properties, measurement precision, and equivalence of the data structures of the two scoring methods.